IDENTIFIKASI KESULITAN DAN STRATEGI MEMBACA PERMULAAN SISWA KELAS RENDAH SEKOLAH DASAR - Muhammad rido; Maulina Hendrik; Agci Hikmawati (Universitas Muhammadiyah Bangka Belitung, 2023)
The background of this research is students who experience difficulties in beginning reading. The purpose of this research is to find out what are the difficulties of student in beginning reading for low grade students in elementary schools and what are the causal factors, and what strategies are used by thee teacher to overcome students who have difficulty reading the beginning. This research is a qualitative type. The method used in this research is the literature study method, the object of which is a relevant study in the form of a scientific article. Data collection techniques in this study are in the form of note-taking techniques. The results showed that in beginning reading for low-grade elementary school students there were still many difficulties in beginning reading, after conducting research from several relevant studies in the form of scientific articles that i had identified, several types of initial reading difficulties were found and also the causative factors. The initial reading difficulties and the strategies implemented by teachers to overcome students who experience initial reading difficulties.